Factorial structure analysis of the Torrance Test with Portuguese students - Primi, Ricardo (2013)
In order to verify the factorial structures of the Torrance verbal and figural tests, two activities of each instrument were applied with 193 students from the 10th and 12th years of education in Portugal. We tried to demonstrate that the collinearity of the fluency and flexibility variables could create methodological artifacts that hinder the understanding of the internal structure underlying the test. The principal component analysis without control of collinearity indicated a solution composed of four basic factors that separeted activities. Controlling for collinearity, we found a new solution, which also contained four factors that, unlike the previous result, grouped variables with similar processes but of different activities. The verbal and figural content is also an important element in the factor structure. This new arrangement makes more sense with the theory that underlies the instruments separating the different processes and content which are being measured by the activities.